Cultura Maker e CTS: constituição de elementos para a consolidação do ensino de Ciências na educação básica - Silva, Fernanda Carminatti Brufatto (2024)
The work aimed to, through analytical research grounded in the Literature Review (LR) and Content Analysis (CA), establish elements that enable the expansion and development of the maker culture, aligned with the Science, Technology, and Society (STS) movement. These elements serve as guidelines for new research in the teaching of Natural Sciences in Basic Education. The study considered both the conception of the maker culture and the utilization of Digital Fabrication Laboratories (Fab Labs) and makerspaces (maker rooms) within the Municipal Department of Education in Araras. Initially, data were outlined through the LR, parameterized for the selection and systemic analysis of publications in the field. Subsequently, data obtained from interviews and questionnaires with Natural Sciences teachers from the municipal education network in Araras were analyzed from the perspective of Content Analysis (CA). The goal was to identify and analyze research that contributes to the construction of robust elements for teaching the discipline. After collecting, analyzing, and discussing the data, a gap in understanding of the topic among the discipline’s educators was observed, prompting a reevaluation of expected outcomes and the proposal of new actions.